Re-humanizing the platform: Content moderators and the logic of care. (June 2020) - Ruckenstein, Minna; Turunen, Linda Lisa Maria
With the goal of re-humanizing discussion platform operations, this study explores the knowledge and aims of commercial content moderators by reframing their work-related ideals through the notion of the "logic of care." In seeking to expand their professional realm by realigning users, moderators, and technical tools, moderators of discussion forums have turned to machines, ideally freeing up resources for real-time interaction between moderators and those who post. By focusing on care, the study calls for technical innovation that integrates moderators' aims with artificial intelligence systems. Rather than acknowledging human skills and resources in terms of moderation tools and discussion culture, the current platform logic forces moderators to operate like machines. Their discontent becomes understandable within a logic that diminishes their skills and vision. The moderator is left with assessing separate posts, rather than offering a meta-perspective to the discussion, overseeing and nurturing it.